Evaluation of utricular and saccular function in BPPV patients: The role of VEMP in diagnosis - Ugur Cengiz, Deniz; Emekci, Tugba; Demirel, Sumeyye; Can Colak, Sanem; Tan, Mehmet (Annals of Medical Research, 2021)
Aim: The pathological cause of Benign Paroxysmal Positional Vertigo (BPPV) is the degeneration of the otolith organs (utricle and sacculus). Vestibular Evoked Myogenic Potentials (VEMP) assess the functions of the otolith organs. The objective of this research was to evaluate the otolith organ functions of patients with unilateral idiopathic BPPV (canalolithiasis of the posterior and lateral semicircular canals) by cVEMP and oVEMP tests. Material and Methods: The study prospectively included 35 patients with BPPV (canalolithiasis of the posterior and lateral semicircular canals) and 30 healthy individuals. Bilateral cVEMP and oVEMP tests were administered to all participants. Participants were divided into three groups: control, BPPV-affected ear, and unaffected ear.Results: In our study, cVEMP and oVEMP abnormalities were statistically significantly different both between the affected and unaffected ear groups and between the affected ear and control groups. There were statistically significant differences in the cVEMP and oVEMP amplitude values both between the affected and unaffected ear groups and between the affected ear and control groups. Also, the asymmetry ratios of the cVEMP and oVEMP tests were statistically significantly different between the case group and the control group. The cVEMP and oVEMP wave latencies (p1, n1, p1-n1) were not statistically significantly different among the BPPV-affected ear, unaffected ear, and control groups. The results of measurements were not statistically significantly different between the posterior and lateral canal involvement subgroups of BPPV patients.Conclusion: Abnormal cVEMP and oVEMP test results, which are observed more frequently in patients with BPPV compared to the control group, indicate utricular and saccular degeneration. Higher oVEMP abnormality ratios compared to those of cVEMP in BPPV patients suggest that utricular dysfunction may be more common than saccular dysfunction.
Keywords: Benign paroxysmal positional vertigo; cervical/ocular vestibuler evoked myogenic; vertigo